The influence of customer satisfaction and service quality on customer loyalty at moh yamin's wedangan - Ar Royan, Halim Muhammad; Setyawan, Anton Agus (Enrichment : Journal of Management, 2023)
The development of the times, many businesses have developed in the food business sector such as restaurants and similar types of businesses. Consumers increasingly understand and understand not service or product quality but also cleanliness that they will consume. The purpose of this study was to determine the effect of customer satisfaction and service quality on customer loyalty at Wedangan Moh Yamin. This research includes quantitative research with 100 respondents. The sampling technique in this study uses non-probablity sampling with the purposive side method. The data collection technique used a questionnaire that was distributed via google form. To analyze the data that has been collected, researchers use the help of SPSS 25.0 software to analyze respondent characteristics and SMARTPLS 3.0 to analyze data. According to the findings of this study, client satisfaction has a good influence on service quality and a positive influence on customer loyalty. Companies can build strong relationships with customers and increase loyalty by focusing on good service and customer satisfaction, which can contribute to business growth. Advice for entrepreneurs is to pay attention to service quality so that customers are satisfied and loyal to the products offered.